Description of Meriania alexandrae (Melastomataceae, Merianieae), a new species of Colombia, and synopsis of the Selvaflorensis complex - Posada-Herrera, Juan Mauricio; Mendoza-Cifuentes, Humberto (Instituto de Ecología, A.C., 2023)
Background and Aims: Meriania is a Neotropical genus of trees and shrubs, comprising approximately 120 species distributed from southern Mexico to Brazil, Bolivia, and the Antilles. In Colombia, associated with the Western and Central Andes, there exists a species complex of Meriania with a set of unique characteristics that distinguishes it from other Andean groups, referred to as the Selvaflorensis complex. The aim of this article is to describe a new species of Meriania associated with this complex, as well as to document the species within this group and their distributions.Methods: Based on a recent collection, the examination of specimens in Colombian herbaria, images in JSTOR Global Plants, and literature on the genus in Colombia, a new species of Meriania is described and illustrated, and categorized according to the IUCN criteria. The Selvaflorensis complex is established within the genus, its relationships are discussed, distinctive traits are documented, a species synopsis is provided, and an identification key and table of primary characteristics for their recognition are presented. Key results: Meriania alexandrae sp. nov. is recognized by its shrubby habit, subpeltate leaves with glandular trichomes, flowers with apiculate and circumscissile calyptras, dimorphic stamens, and filiform seeds. It is endemic to Colombia, and it is suggested to be Endangered (EN). Together with four other species, it constitutes the new complex referred to as Selvaflorensis, characterized by the presence of glandular trichomes on leaves, calyptrate flowers, and filiform seeds. This complex is restricted to the biogeographical region known as the Western Cordillera of Colombia. Additionally, as a result of collection review, two paratypes previously associated with Meriania silverstonei are reassigned to this new species.Conclusions: The Selvaflorensis complex is a natural group within Meriania, restricted to the northern Andes, currently composed of five species, and it is not closely related to the Brachycera group.